Asymptotic formulas for the left truncated moments of sums with consistently varying distributed increments - Sprindys, Jonas; Šiaulys, Jonas (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we consider the sum Snξ = ξ1 + ... + ξn of possibly dependent and nonidentically distributed real-valued random variables ξ1, ... , ξn with consistently varying distributions. By assuming that collection ξ1, ... , ξn follows the dependence structure, similar to the asymptotic independence, we obtain the asymptotic relations for E((Snξ)α1(Snξ > x)) and E((Snξ – x)+)α, where α is an arbitrary nonnegative real number. The obtained results have applications in various fields of applied probability, including risk theory and random walks.